Pengaruh Intellectual Capital Terhadap Kinerja Keuangan - Feby Astrid Kesaulya; Cellvia Christina (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2019)
This study aims to prove whether intellectual capital affects the financial performance of the food and beverages companies listed in Indonesia Stock Exchange. The population of this research are food and beverages companies listed in Indonesia Stock Exchange on the years of 2016-2018 or during observation period. Samples are taken by using the purposive sampling technique which resulted in 13 companies as samples, and 56 firm years in total. The independent variable is intellectual capital measured by VAIC, while the dependent variable is financial performance measured by ROA. The hypothesis is tested by using simple regression analysis. The result shows that intellectual capital cannot be a predictor of financial performance in food and beverages companies listed in IDX. It can be concluded that some companies cannot manage their asset in optimal manner. This is causing an inability to create the competitive advantage which is important to increase companies’ financial performance.